2021
DOI: 10.3389/fendo.2020.630948
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Stress Impact in the Paternal Germ Cells Epigenome: Can Catecholamines Induce Epigenetic Reprogramming?

Abstract: Spermatogenesis is characterized by unique epigenetic programs that enable chromatin remodeling and transcriptional regulation for proper meiotic divisions and germ cells maturation. Paternal lifestyle stressors such as diet, drug abuse, or psychological trauma can directly impact the germ cell epigenome and transmit phenotypes to the next generation, pointing to the importance of epigenetic regulation during spermatogenesis. It is established that environmental perturbations can affect the development and beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 79 publications
0
4
0
1
Order By: Relevance
“…Stress is an important phenomenon for survival that requires prompt physiological and behavioral responses for an individual to cope with the different situations in the environment and maintain body homeostasis ( 27 ). Physiologically, stress response can be categorized into the fast response mediated by the sympathoneural and sympathoadrenomedullary (SAM) axis and the slow response mediated by the hypothalamic-pituitary-adrenal axis (HPA) ( 28 ).…”
Section: Gnihmentioning
confidence: 99%
See 2 more Smart Citations
“…Stress is an important phenomenon for survival that requires prompt physiological and behavioral responses for an individual to cope with the different situations in the environment and maintain body homeostasis ( 27 ). Physiologically, stress response can be categorized into the fast response mediated by the sympathoneural and sympathoadrenomedullary (SAM) axis and the slow response mediated by the hypothalamic-pituitary-adrenal axis (HPA) ( 28 ).…”
Section: Gnihmentioning
confidence: 99%
“…In addition, the activation of the first line of the stress response stimulates the slow response, which is mediated by the activation of the HPA axis to release glucocorticoids ( 28 ). Corticotropin-releasing hormone (CRH) is secreted from the paraventricular nucleus (PVN) of the hypothalamus and binds to its receptors (CRH-R1 and CRH-R2).…”
Section: Gnihmentioning
confidence: 99%
See 1 more Smart Citation
“…Prenatal stress exposure has been linked to neurodevelopment and the risk of neuropsychiatric disorders in offspring [ 79 ]. Retrospective epidemiological studies have provided compelling evidence linking lifetime stress exposure in men with disease risk in offspring [ 80 ]. The rodent studies have demonstrated the susceptibility of germ cells to stressful environments throughout the paternal lifetime [ 81 ].…”
Section: Early Life Adverse Exposure and Future Disease Riskmentioning
confidence: 99%
“…Качество семени зависит от физиологического статуса самца и определяет его роль в воспроизводстве потомства, которая не ограничивается собственно оплодотворением самки. Выяснено, что характер реакции на стресс в следующем поколении определяется девятью видами микроРНК (miRNA), которые присутствуют в сперме (35,36). Изменения, вызванные внешними факторами, наследуются от отцов через метилирование ДНК сперматозоидов, модификацию белков, участвующих в упаковке ДНК, а также через эпигенетические модификации, вызванные изменением состава и структуры РНК, содержащейся в сперме, следовательно, самцы, находящиеся в хроническом стрессе, производят потомство со значительно ослабленной стрессовой реакцией во взрослом возрасте (37).…”
unclassified